2021
DOI: 10.1111/jep.13615
|View full text |Cite
|
Sign up to set email alerts
|

Which symptoms best distinguish fibromyalgia patients from those with other chronic pain disorders?

Abstract: Rationale, aims and objectives: The primary purpose of this study was to test both classic and novel FM pain and non-pain symptoms to determine their practical efficacy in aiding clinicians to distinguish FM pain from other chronic pain disorders.Methods: 158 pain patients from two primary care clinics were evaluated with history, physical exam, chart review, and a questionnaire containing 26 exploratory symptoms (10 from the Symptom Impact Questionnaire (SIQR) and 16 from the FM literature)). The symptoms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It has been evident that the subjective character of symptoms, the absence of a diagnostic test, and the modest response to treatments remain challenges for treating healthcare professionals in standard clinical practice [ 9 ]. As well, the presence of several somatic complaints confounds the condition, and the diagnosis of FM is frequently overlooked [ 21 ]. Definitely, a well-informed physician and good communication with the patients could reliably reach valid FM diagnoses [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been evident that the subjective character of symptoms, the absence of a diagnostic test, and the modest response to treatments remain challenges for treating healthcare professionals in standard clinical practice [ 9 ]. As well, the presence of several somatic complaints confounds the condition, and the diagnosis of FM is frequently overlooked [ 21 ]. Definitely, a well-informed physician and good communication with the patients could reliably reach valid FM diagnoses [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, another study has found that the descriptors of central sensitivity-related pain differ from those of disease activity-related pain (35). Two recent studies (36,37) have investigated the differentiation of FM from other chronic pain disorders or myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), which is also very co-morbid. The first evaluated 158 pain patients attending two primary care clinics, and found that five symptoms best distinguished FM from other chronic pain disorders: persistent deep aching over the body, poor balance, environmental sensitivity, tenderness to touch, and pain after exercise.…”
Section: Reviewmentioning
confidence: 99%
“…As far as fibromyalgia’s etiology is undiscovered, the disease does not have a well-established animal model that mimics all the signs and symptoms of the complex illness. Patients with fibromyalgia have, in addition to their spontaneous widespread pain, disproportionally increased pain in response to painful stimuli (“mechanical hyperalgesia”) [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%